2021
DOI: 10.1111/aos.14940
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for macular oedema after primary rhegmatogenous retinal detachment surgery: a prospective single‐centre study

Abstract: Purpose To assess the incidence of cystoid macular oedema (CME) diagnosed by spectral domain optical coherence tomography (SD‐OCT) after primary rhegmatogenous retinal detachment (RRD) surgery. Methods From April 2016 to October 2017, 150 eyes of 150 patients presenting with primary RRD were included consecutively in this prospective single‐centre study. Patients with the following characteristics were excluded: previous vitreoretinal surgery, combined cataract surgery, preoperatively presentation with any int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Our results differ from those of some recent reports in this setting. Specifically, in a 6-week prospective study, Gebler et al 4 reported a CME rate of 16.3% for the PPV and 20.7% for the SB patients and found no differences between the procedures. 4 Overall, considering the short follow-up, the rate of CME in this study is higher than in our findings, especially in the SB cases.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results differ from those of some recent reports in this setting. Specifically, in a 6-week prospective study, Gebler et al 4 reported a CME rate of 16.3% for the PPV and 20.7% for the SB patients and found no differences between the procedures. 4 Overall, considering the short follow-up, the rate of CME in this study is higher than in our findings, especially in the SB cases.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, in a 6-week prospective study, Gebler et al 4 reported a CME rate of 16.3% for the PPV and 20.7% for the SB patients and found no differences between the procedures. 4 Overall, considering the short follow-up, the rate of CME in this study is higher than in our findings, especially in the SB cases. This discrepancy could be attributed to the extensive use of gas tamponade, injected in 65.5% of their SB procedures, as an adjunctive tool to achieve retinal reattachment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fig. S1) [16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Eight (44.44%) studies explicitly excluded and/or did not have any baseline eyes with PVR grade C or worse, nine (50%) excluded eyes with a history of ocular trauma, seven (38.89%) excluded eyes with macular hole, and nine (50%) excluded eyes with previous vitreoretinal surgery.…”
Section: Baseline Demographic Characteristicsmentioning
confidence: 99%
“…In the main analysis, the removal of one study at a time resulted in final BCVA being significantly better with SB alone [32] and a higher incidence of IOP elevation with SB + PPV with the cited references removed from analysis [41]. Final reattachment rate [39,43] as well as the incidence of macular edema [29,41,45,48] and cataract development or progression were no longer significantly different between SB + PPV and SB alone upon individual removal of the cited references from analysis [40][41][42][43].…”
Section: Sensitivity Analysis: Leave-one-outmentioning
confidence: 99%